Peran Biomekanika dalam Pencegahan Cedera pada Atlet Karate : Suatu Review Sistematis - Mohammad Noval Baghaskara; Muhammad Zaidan Barki Muslim; Abdul Aziz Hakim; Achmad Widodo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the role of biomechanics in preventing injuries in karate athletes through a systematic review. The research method follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework with a literature search in the Science Direct database, Google Scholar, and the use of tools such as VOSviewer and Publish or Perish. Studies that met the inclusion criteria (10 articles) were analyzed to identify injury patterns, biomechanical factors, and prevention strategies. The results showed that the most common injuries in karate athletes were contusions, calf muscle strains, and finger sprains, which were related to force distribution, extreme joint angles, and postural control. Biomechanical analysis (motion capture, EMG, force plate) proved that technique correction, proprioception training, stabilizing muscle strengthening, and balance training could reduce the risk of injury by up to 20%. Significant differences were found between novice and elite athletes in terms of movement consistency and neuromuscular control. The integration of biomechanical principles with karate philosophy (mushin, zanshin, kime) was also emphasized to maintain a balance between performance and cultural values. Limitations of the study include heterogeneity of measurement instruments and potential publication bias. Future recommendations include longitudinal studies, development of portable devices (IMUs), and personalization of training programs based on individual biomechanical profiles